Case Report: Eighteen Month Relapse- Free Survival Following Radical Multidisciplinary Oncological Treatment in a 68-Year-Old Male Patient With Histiocytic Sarcoma - Wehrmann, Stefan; Rudolph, Hagen; Ernst, Dominikus; Siepmann, Timo; Kaltofen, Dorothea; Hänel, Mathias; Mirow, Lutz (Frontiers in Oncology, 2021)
Introduction: Histiocytic Sarcoma (HS) is a rare and agressive malignancy, and patients can present with rapid tumor growth and invasion. The optimal diagnostic and therapeutic management is unknown since only a few cases have been published. Here we report a patient with histiocytic sarcoma of the right groin. Case: A 68 year-old male patient presented to our hospital with suspicion of a superinfected atheroma of the right groin. Computed tomography showed an abdominal tumor of unknown entity. Detailed assessment including immunohistochemically evaluation of biopsy material confirmed HS. The patient underwent radical tumor resection including compartment-resection of the right thigh. During five additional cycles of chemotherapy over a period of 1.5 years he remained relapse-free. Summary: Diagnostic work up and treatment of HS is challenging, as there is a paucity of clinical reports and lack of standard guidelines for care. In the present case report, aggressive multidisciplinary treatment resulted in good clinical outcome, however, further studies evaluating this approach in similar patients are needed.